1980
DOI: 10.1017/s0022149x00006398
|View full text |Cite
|
Sign up to set email alerts
|

Immunodiagnosis of human filariasis by counterimmunoelectrophoresis using Litomosoides carinii antigens

Abstract: The presence of precipitin antibody and soluble circulating antigen was demonstrated in sera of individuals with clinical filariasis by counterimmunoelectrophoresis. Antigens derived from Litomosoides carinii and antisera raised in rabbits to the adult worm antigens were used for the detection of antibody and antigen in human sera. Of 35 subjects, 2 had microfilariae in the peripheral blood, 9 soluble circulating antigen, 19 antibody in sera, and 6 had both antigen and antibody. It suggests that 5.7% of cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…These observations are perhaps not surprising in view ofthe well-established crossreactivity between crude extracted "antigens" from whole filarial worms (see e.g., Subrahmanyam etal. 1974, Dissanayake& Ismail 1980, Dasgupta et al 1980 or the ability of sera from patients with different filarial infections to bind to B pahangi microfilariae in fluorescent tests . It is interesting to speculate how evolutionary pressures have not resulted in exposed surface molecules of these parasites becoming completely species-specific: do they perform an essential function for the worm, or is there even some advantage to the parasite in possessing crossreactive epitopes?…”
Section: Assessment Of Crossreactivitvmentioning
confidence: 99%
“…These observations are perhaps not surprising in view ofthe well-established crossreactivity between crude extracted "antigens" from whole filarial worms (see e.g., Subrahmanyam etal. 1974, Dissanayake& Ismail 1980, Dasgupta et al 1980 or the ability of sera from patients with different filarial infections to bind to B pahangi microfilariae in fluorescent tests . It is interesting to speculate how evolutionary pressures have not resulted in exposed surface molecules of these parasites becoming completely species-specific: do they perform an essential function for the worm, or is there even some advantage to the parasite in possessing crossreactive epitopes?…”
Section: Assessment Of Crossreactivitvmentioning
confidence: 99%
“…L. carinii adult worms were collected from the pleural cavity of infected albino rats, and the antigens were prepared by the methods described elsewhere (Dasgupta et al 1980). In brief, the adult worms were washed in PBS, homogenized and sonicated.…”
Section: Preparation Of Antigenmentioning
confidence: 99%
“…A requirement for a large quantity of antigens and the difficulty in obtaining their supplies from homologous species for the detection of antibody have restricted their use in routine practice. The detection of antibody has been further restricted by an interference due to the presence of soluble antigens (Franks 1946, Dasgupta & Bala 1978, Dasgupta et al 1980) and immune complexes (Dasgupta & Bala 1978, Dissanayake et al 1982 in circulation. The detection of soluble circulating antigens (SCA), on the other hand, has always been thought to be easily interpretable and considerably more informative than serum antibodies in nematode infections, in particular with parasite dwelling in the lymphatics and circulating in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some investigators have reported the detection of circulating parasite antigens in canine and human filariasis [5][6][7]. The present study describes a dot enzyme-linked immunosorbent assay (Dot-ELISA) using nitrocellulose (NC) paper to detect circulating D. immitis antigens (CDA) in the sera from dogs and demon-0920-8534/88/$03.50 .5 1988 Federation of European Microbiological Societies strates its possible use as a clinical diagnostic method for canine dirofilariasis.…”
Section: Introductionmentioning
confidence: 99%